IMMNUNOMODUlATORY AND CYTOTOXIC EFFTECTS OF AQUEOUS LEAF EXTRACTS OF CERTAIN PlANTS ON COMMON CARP, CYPRINUS CARPIO - Kiran Kumar, N.; Pani Prasad, K.; Mukherjee, S. C. (Journal of Indian Fisheries Association, 2008)
Effect of aqueous leaf extracts of Catheranthus roseus, Calotropis gigantium and Datura stromoneum on common carp, Cyprinus carpio were investigated. C. carpio were separately fed with 1 and 2% aqueous extracts of these three plant leaves for a period of seven days. In 1% Catheranthus roseus of leaf extract fed group no significant tissue level changes were recorded.One and 2% of other two species fed treated group showed mild to severe necrotic and cellular changes in liver, kidney and spleen. Immunologically, significant rise in antibody titre and respiratory burst activity was recorded for 1% Catheranthus roseusfed group. Keywords: Cyprinus carpio, Catheranthus roseus, Calotropis gigantium, Datura stromoneum, E.tarda.